Prevalence Of Microalbuminuria as A Marker of Incipient Nephropathy in Type 2 Diabetes Patients at SMIMER Hospital, Surat - Chavan, Vilas U.; Ramavataram, DVSS; Miyani, Kinjal L.; Lad, Hasit D.; Nilakhe, S.D. (National Journal of Community Medicine, 2014)
Background: Diabetic nephropathy (DN) is one of the most significant long-term complications in diabetes mellitus (DM). The study was primarily aimed to screen type 2 DM patients for renal damage and to find out the prevalence of MAU as marker of nephropathy in the SMIMER hospital, Surat. Methods: We studied 82 known cases of type 2 DM and 50 healthy subjects as control. Plasma glucose, serum lipid profile, urea, uric acid, creatinine and urine albumin and creatinine were measured in subjects. Based on urine albumin and albumin:creatinine ratio (ACR) stages of nephropathy were diagnosed. Data was expressed as mean ± SD and data was compared by using unpaired student ‘t’ tests for independent sample. Results: We found significantly higher levels of fasting and post prandial glucose (P<0.05), urea (P<0.01), uric acid (P<0.03), urine albumin and ACR (P<0.05) in DM patients compared to controls. We observed increased level of total cholesterol (P<0.05), triacylgycerol (P<0.05) and non significant decrease in HDL level ((P=0.11) in DM patients compared to controls. In DM patients the prevalence of normoalbuminuria, microalbuminuria and macroalbuminuria were 21.95%, 62.19% and 15.85% respectively. Conclusion: Our study concludes that MAU is a reliable marker of DN in type 2 DM patients. MAU and dyslipidemia together may be more potent risk factor for complications in type 2 DM. Therefore regular screening for MAU is recommended for all asymptomatic DM patients for reducing cardiovascular risks and slowing the progression to end-stage renal disease to reduce the socioeconomic burden of DM.